PIXELS AND PROFITS: RETHINKING TAX POLICY FOR THE BORDERLESS DIGITAL ECONOMY - S. Chandralekha; S. Dharani; S. Aruna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India’s digital economy has grown rapidly in recent years due to greater internet use, mobile technology, and many startups. As more people and businesses go online, traditional tax systems are struggling to keep up. New types of online services—like e-commerce, digital ads, cloud storage, and online content—are making money across borders, often without a physical presence. This creates confusion about where and how these businesses should be taxed. In the 2022–2023 budget, the Indian government introduced a 30% tax on virtual digital assets (like cryptocurrencies). Globally, countries like the UK and France also started taxing big tech companies to ensure they pay taxes in the countries where they operate. This article highlights how current international tax rules are outdated and need urgent changes. Right now, many rules are based on physical presence in a country, which doesn’t work well for digital businesses. Some companies avoid taxes by shifting profits to countries with low tax rates. These practices need to be revised to apply digital taxes fairly. The article explains what the digital economy is and how Indian tax laws are falling behind new digital trends. It also discusses the need for international agreement on key tax rules so that all countries can apply similar and fair laws. The author uses existing studies to explore these issues and suggests how tax laws can be improved to bring the digital economy into the mainstream and make it more transparent. Finally, the article offers possible solutions to better tax digital businesses and technologies.